Influence of load, sliding speed, and temperature on the tribological behavior of plasma sprayed BaF2-doped YSZ composite coatings - Das, Rajib; Bandyopadhyay, P.P. (Journal of the European Ceramic Society, 2025)
This report explores the tribological characteristics of BaF2-doped YSZ coatings under varying loads, speeds, and temperatures. Up to 10 N load, the friction coefficient (COF) decreases owing to elastic contact, then it stabilizes within 0.78 – 0.80 as plastic contact dominates. At 650 °C, BaF2 extrusion under high loads reduces the COF to 0.56. Increased speed further lowers the COF through debris ejection and asperity softening. The wear rate rises with load and speed owing to Hertzian stress and tangential impact, respectively. Fatigue and abrasive wear are the main wear mechanisms. BaF2 layer provides significant wear protection, and with temperature, its shear strength reduces, lowering the COF to 0.39 and wear rate to 5.36 × 10−4 mm3/Nm at 750 °C. •BaF2 extrusion at high contact pressure inside wear track at 650 °C.•Debris ejection and asperity softening at high speed causing friction reduction.•Drop in BaF2 hardness with temperature leads to minimum friction (0.39) at 750 °C.•Lowest wear at 750 °C due to lower friction and BaF2 layer protection.•Residual stress and phase transformation toughening do not influence wear.